Antibiotics to modify sickle cell disease vaso-occlusive crisis?. (November 2021) - Stewart, Connor; Jang, Tim; Mo, George; Mohamed, Nader; Poplawska, Maria; Egini, Ogechukwu; Dutta, Dibyendu; Lim, Seah H.
Abstract: Despite the availability of hydroxyurea, the clinical use of the medication among patients with sickle cell disease (SCD) remains low in the United States. Given the high healthcare utilization cost, SCD requires new therapeutic approaches. Recent studies demonstrated bacterial overgrowth and dysbiosis-related intestinal pathophysiological changes in SCD. Intestinal microbes regulate neutrophil ageing. Aged and activated neutrophils contribute to the pathogenesis of vaso-occlusive crisis (VOC) in SCD. In this paper, we will review the pre-clinical and clinical data on how antibiotics might reduce the intestinal microbial density and influence the course of VOC. Based on these observations, we will discuss rationales for and potential challenges to antibiotic-based therapeutic approaches that may modify the clinical course of VOC in SCD.